2011
DOI: 10.1002/lary.22146
|View full text |Cite
|
Sign up to set email alerts
|

ORL emergencies boot camp: Using simulation to onboard residents

Abstract: An intensive, simulation-based Boot Camp addressing airway, bleeding, and other otolaryngology emergencies was successful in improving junior otolaryngology residents' confidence and was perceived as useful in developing knowledge, technical skills, self-confidence, and improving clinical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(143 citation statements)
references
References 17 publications
4
136
0
3
Order By: Relevance
“…Other studies have also shown similar results in medicine and the field of otolaryngology [17,18]. All of these studies have consistently shown that through simulation and boot camp training, residents began developing the appropriate knowledge, skill set and self-confidence [2,7] needed to succeed during residency and, more importantly, that these skills transferred to real clinical situations/procedures with real patients.…”
Section: Idea and Innovationmentioning
confidence: 62%
See 2 more Smart Citations
“…Other studies have also shown similar results in medicine and the field of otolaryngology [17,18]. All of these studies have consistently shown that through simulation and boot camp training, residents began developing the appropriate knowledge, skill set and self-confidence [2,7] needed to succeed during residency and, more importantly, that these skills transferred to real clinical situations/procedures with real patients.…”
Section: Idea and Innovationmentioning
confidence: 62%
“…In otolaryngology, the ultimate goal is to transition "undifferentiated senior medical students to dedicated otolaryngology residents [3]." With the advent of duty hour restrictions and resource limitations, training a resident in a shorter period of time and in a more modifiable environment is being more heavily favored than traditional teaching of only experiencing a medical emergency in a real-life situation [2,3,7,12,13]. By putting these skills into a boot camp style course, residents are given the opportunity to participate in intense-style training while still being taught in a safe, simulated environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…anesthesiology, intensive care, emergency care), in pediatrics and obstetrics (overview see [50]), the simulation training is more and more often found in otorhinolaryngology. In particular the dynamic environment of the ENT-specific outpatient clinic where the staff members are confronted with high-risk emergency cases such as obstruction of the airways, bleedings, and allergic reactions is appropriate for teaching basic skills of teamwork [51], [52], [53]. …”
Section: Team Training In Otolaryngologymentioning
confidence: 99%
“…The positive effect of distributed practice can be attributed to time dependent consolidation of memory 57 and even for a simple procedure such as myringotomy, spacing practice by a single day is insufficient in improving novice performance 58 . Therefore, the increasingly popular “ORL surgical boot camps” 59,60 with simulation-based, massed practice of a range of surgical skills may have limited long term effectiveness for learning otologic skills.…”
Section: Introductionmentioning
confidence: 99%